Bryostatin enhances CD20 CAR-T therapy efficacy against B-cell lymphoma by overcoming trogocytosis-mediated antigen loss - Wang, Xiaofeng; Sun, Keran; Zhang, Zhengzheng; Zhang, Ling; Cui, Ling; Song, Shuxia; Wei, Lin (Frontiers in Immunology, 2026)
IntroductionTrogocytosis, an active membrane transfer process, impairs the therapeutic efficacy of CAR-T cells by inducing antigen loss from tumor cells. This study investigated whether Bryostatin, a PKC modulator derived from marine organisms, could enhance CD20 CAR-T cell activity by up-regulating the CD20 antigen on tumor cells and promoting T cell activation, differentiation and function.MethodsCD20 antigen expression and trogocytosis-mediated membrane transfer were assessed by flow cytometry and immunofluorescence following co‑culture of CD20 CAR‑T cells with Raji or BALL‑1 cells. Trogocytosis‑positive (Trog⁺) CAR‑T cell cytotoxicity and fratricide by fresh CAR‑T cells were evaluated by ELISA. Proteomic profiling compared metabolic features of Trog⁺ and Trog⁻ CAR‑T cells. Using flow‑sorted BALL‑1 subsets with differential CD20 expression (CD20low, CD20mid, CD20hi), we examined how antigen density affects CAR‑T persistence and killing. Finally, Bryostatin‑mediated CD20 upregulation and its therapeutic impact on CAR‑T efficacy were tested in vitro and in a murine subcutaneous lymphoma model.ResultsUpon contact with Raji or BALL-1 cells, CD20 CAR‑T cells underwent trogocytosis, leading to marked loss of tumor‑cell CD20 and impaired cytotoxicity of trogocytosis‑positive (Trog⁺) CAR‑T cells, which also became susceptible to fratricide. CD20 antigen density positively correlated with CAR‑T killing efficacy. Proteomic analysis revealed that Trog⁺ CAR‑T cells exhibited enriched activity in ribosome biogenesis, mRNA surveillance, and RNA catalysis, suggesting elevated protein synthesis alongside exhaustion features. Key MEK/ERK‑related transcription factors (c‑JUN, TCF7) linked to T‑cell activation were downregulated in Trog⁺ cells. In both in vitro and mouse lymphoma models, Bryostatin potentiated CD20 CAR‑T‑mediated tumor suppression. Mechanistically, bryostatin upregulated CD20 expression in tumor cells via the MEK/ERK pathway and enhanced c‑JUN/TCF7 levels in CAR‑T cells, promoting their tumor infiltration.ConclusionBryostatin enhances CD20 CAR‑T efficacy by counteracting trogocytosis‑driven antigen loss and upregulating CD20 expression, providing a promising strategy to overcome antigen escape in lymphoma therapy.